Development of a Web-Mobile Based Attendance Information System For Teachers and Students Using QR Code Integrated With Geolocation - La Ode Muhammad Nurfansyah; Wahyu Sri Utami (Universitas Islam Kuantan Singingi, 2025)
This research aims to develop a web-based and mobile-based academic information system to simplify the process of recording student attendance at SMPN 33 Buton. The manual attendance system creates various obstacles such as delays in recording, data inaccuracy, and difficulties in monitoring. This system is designed using the Waterfall development method which includes the stages of needs analysis, design, implementation, testing, and deployment. Web technology is used for the admin and teacher dashboards, while mobile technology is used by students to record attendance. The system backend is supported by a structured database to ensure the efficiency and accuracy of data processing. The results of the development show that this system can simplify the process of recording student attendance and help the school in managing attendance data more effectively.